The relationship between breast cancer and thyroid autoimmune disorders in southeast Iran: A case-control study - Nosratzehi Shahin; Hashemi Seyed Mehdi; Payandeh Abolfazl; Bolouri Ahmad; Okati Fahimeh (Endocrine Regulations, 2024)
Objective. To better understand the role of thyroid hormones in regulating the growth of breast epithelial cells and the estrogen-like effects of these hormones, the present study was conducted to investigate the relationship between breast cancer and thyroid autoimmune disorders in southeast Iran women.